2017
DOI: 10.3389/fnhum.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Systems, Subjects, Sessions: To What Extent Do These Factors Influence EEG Data?

Abstract: Lab-based electroencephalography (EEG) techniques have matured over decades of research and can produce high-quality scientific data. It is often assumed that the specific choice of EEG system has limited impact on the data and does not add variance to the results. However, many low cost and mobile EEG systems are now available, and there is some doubt as to the how EEG data vary across these newer systems. We sought to determine how variance across systems compares to variance across subjects or repeated sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 40 publications
6
56
0
1
Order By: Relevance
“…Classically, EEG was considered a low mobility tool because it required strict control of the movements and surroundings of participants, which limits it to the lab environment. However, in the last years, the development of new technologies has allowed for improvement in mobility by creating mobile EEG systems (Melnik et al, 2017). Such systems are a great tool to study social interactions.…”
Section: Eeg/megmentioning
confidence: 99%
“…Classically, EEG was considered a low mobility tool because it required strict control of the movements and surroundings of participants, which limits it to the lab environment. However, in the last years, the development of new technologies has allowed for improvement in mobility by creating mobile EEG systems (Melnik et al, 2017). Such systems are a great tool to study social interactions.…”
Section: Eeg/megmentioning
confidence: 99%
“…For each subject and channel, the data were z ‐transformed, that is, the mean of all samples of the respective subject and channel was subtracted from each sample and this difference was divided by the standard deviation. Please note that large inter‐individual differences exist in EEG signals (Melnik et al., ). However, as a consequence of this z‐transformation all subjects contribute equally to the grand average.…”
Section: Methodsmentioning
confidence: 99%
“…Given a suitably structured corpus of data, multi-factor statistical modeling e.g., using ANOVA, can be valuable in characterizing different sources of variability. For example, in a controlled experiment using a multi-factor design, Melnik et al (Melnik et al, 2017) showed that subject variability dominated differences in event-related potentials, followed by headset type in specific experimental paradigms. Additionally, explicitly modeling recording-and study-specific variability in a multi-level partial-pooling analysis can also help address issues with inflated inferential certainty associated with classical full-pooling analyses.…”
Section: Channel Analysismentioning
confidence: 99%